Revaccination with Bacille Calmette-Guérin (BCG) is associated with an increased risk of abscess and lymphadenopathy - Paola Villanueva; Ushma Wadia; Nigel Crawford; Nicole L. Messina; Tobias R. Kollmann; Michaela Lucas; Laurens Manning; Peter Richmond; Laure F. Pittet; Nigel Curtis (npj Vaccines, 2022)
Abstract The reported frequency and types of adverse events following initial vaccination and revaccination with Bacille Calmette-Guérin (BCG) varies worldwide. Using active surveillance in a randomised controlled trial of BCG vaccination (the BRACE trial), we determined the incidence and risk factors for the development of BCG injection site abscess and regional lymphadenopathy. Injection site abscess occurred in 3% of 1387 BCG-vaccinated participants; the majority (34/41, 83%) resolved without treatment. The rate was higher in BCG-revaccinated participants (OR 3.6, 95% CI 1.7–7.5), in whom abscess onset was also earlier (median 16 vs. 27 days, p = 0.008). No participant with an abscess had a positive interferon-gamma release assay. Regional lymphadenopathy occurred in 48/1387 (3%) of BCG-vaccinated participants, with a higher rate in revaccinated participants (OR 2.1, 95% CI 1.1–3.9). BCG-associated lymphadenopathy, but not injection site abscess, was influenced by age and sex. A previous positive tuberculin skin test was not associated with local reactions. The increased risk of injection site abscess or lymphadenopathy following BCG revaccination is relevant to BCG vaccination policy in an era when BCG is increasingly being considered for novel applications.